Careers if you like to travel - Parks, Peggy J., 1951- (Career exploration (ReferencePoint Press), 2020)
Introduces a variety of careers in the travel industry, providing information about educational requirements, job duties, work environments, salaries, and employment outlook. Includes color photographs, an interview with a professional in the field, and quotes.